PENGARUH PERSEPSI BAGI HASIL TERHADAP MINAT MENABUNG DI BANK BNI SYARIAH KCP PALEMBANG - Pajaria, Yusiresita; Lestari, Ria (Sekolah Tinggi Ekonomi Dan Bisnis Islam Darussalam, 2020)
This study examines the effect of the perception of profit sharing on the interest in saving at the BNI Syariah KCP Palembang bank. The purpose of this study was to determine and explain how the perception of profit sharing affects the interest in saving at the BNI Syariah KCP Palembang bank. This research is a quantitative research with the data source used is questionnaire data. The number of samples used in the study were 100 respondents, the sampling technique was accidental sampling technique. The method used in this research is simple linear regression analysis. The results showed that the profit sharing perception variable had a significant positive effect on the interest in saving at the BNI Syariah KCP Palembang bank, this was evidenced by the partial test results which showed that the value of tcount> ttable (2.569> 1.98447) and a significant value of 0.012 <0, 05.